Assessment of immune response in cattle against experimentally prepared trivalent (O, A, and Asia-1) FMD vaccine in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2015)
This research work was conducted to investigate the effects  of  age,  sex  and  breed  on  the  induction  of immune  response  against  experimentally  prepared inactivated  trivalent  (type  O,  A,  and  Asia-1)  FMD vaccine. Twenty six cattle were divided into four test groups (Group A, B, C, and D; 5 cattle in each group) and one control group (n=6) based on breed (local and cross),  age  (?12  months  and  >12  months),  and  sex (male  and  female).  Test  cattle  were  vaccinated  with the  experimentally  prepared  trivalent  FMD  vaccine. Pre-  and  post  vaccinated  sera  from  the  vaccinated cattle were collected upto 63 days, and the sera were tested  using  liquid  phase  blocking  enzyme  linked immunosorbent  assay  (LPBE)  that  was  specific  for FMD  serotypes  O,  A,  and  Asia-1.  Antibody  titers  of all  the  pre-vaccinated  serum  samples  were  found  to be under protection level. The females were found to be more protected (90%; n=9/10) as compared to males (70%;  n=7/10).  The  titers  obtained  were  statistically analyzed  using  ttest  to  observe  the  effects  of  age, breed and sex. It was observed that the mean values of antibody titer in cattle aging >12 months against O, A,  and  Asia-1  serotypes  were  significant  (P12  months  showed  better immune response towards trivalent FMD vaccine. http://dx.doi.org/10.5455/javar.2015.b121